L’exploitation familiale au regard de l’histoire longue du développement rural en France (19e – 20e siècles) - Pierre Cornu (Bulletin de l’Association de Géographes Français)
Our present time is deeply concerned with the questions of sustainability and resilience of agricultural production systems. In this situation, territorialized family farming reappears as a legitimate inquiry object, not only in a strict economical dimension, but also in an ecosystemic conception of development. Which resources can be expected from this kind of agriculture? To which degree is it realistic to reinvent it? Those questions, which are formulated in a prospective way, actually raise a profound historical interrogation. Which legacies, what kind of continuity should be examined? In order to assess the true importance of historical perspective in the multidisciplinary debate about family farming, our paper proposes a methodical review of the “great narrative” of agricultural and rural development. First, it reconsiders the common preconception of the link between family and exploitation in 19th century France. Then, it enlightens the fact that family farming has had many economical shapes out of mere agriculture in the first part of the 20th century. At last, it questions the idea of the decline of this “family model” at the advent of the “silent agricultural revolution” of the 1950’s and 1960’s.